Subsolidus phase equilibria in the GdFeO3-SrFeO3-δ system in air. Issue 15 (15th October 2020) - Тugova, Е.А.; Кrasilin, А.А.; Panchuk, V.V.; Semenov, V.G.; Gusarov, V.V.
Abstract: The paper considers phase equilibria in the subsolidus region of the GdFeO3 -SrFeO3-δ system in air. By using X-ray powder diffraction, SEM/EDS, and Mössbauer spectroscopy, a GdFeO3 -SrFeO3-δ phase diagram was constructed in the 1300–1500 °C temperature range. The samples of Gd1-x Srx FeO3- α for this study were synthesized by solid-phase chemical reactions. The study of phase equilibria in the GdFeO3 -SrFeO3-δ system showed the presence of three areas, that is, of solid solutions based on the strontium-poor GdFeO3 orthorhombic phase, of the strontium-rich SrFeO3-δ cubic phase, as well as of an intermediate region in the mixture of these phases. The miscibility gap width (Δ x ) decreases from 0.54 to 0.35 with an increase in temperature from 1300 to 1500 °C.